Types and characteristics of the oxbow-lakes in Lower-Tisza-valley - classification from landscape planning perspective - Molnár, Zsófia (Acta Geographica Debrecina Landscape & Environment series, 2013)
The study area is located in Hungary on the South of the Great Plane called Alföld in Hungarian. There are ten oxbow lakes are located in the region of the Lower Tisza Valley. The quality of the area’s oxbow lakes are rather different. There are protected, highly valuable sites in terms of landscape and nature conservation, yet degraded areas utilized for economic purposes can also be found. In the course of river-control in the Lower Tisza Valley was affected by the 84-90th cutoffs, therefore oxbows have been formed in the area. Four of these oxbows are on the part that is not effected by floods, and six of them are located in the active floodplain.The attributes or usage of oxbow lakes allow for a complex system of categorisation. The assessment and classification of oxbow lakes can establish the grounds for assessment, as well as for planning the interventions of landscape restoration.